Direct medical costs of type 2 diabetes in China: a multicentre, prospective cohort study. (November 2016) - Li, Xiang; Xu, Zhangrong; Weng, Jianping
Abstract: Background: We aimed to investigate the direct medical costs of type 2 diabetes and factors affecting such costs in China. Methods: In this multicentre, prospective cohort study, we recruited outpatients and inpatients with type 2 diabetes from 16 tertiary hospitals in 14 major cities of China. We followed-up patients for 6 months and collected patient data (including outpatient visits, hospital admissions, treatments, hypoglycaemia, and self-monitoring of glucose) and direct medical costs monthly. Log-transformed direct medical costs were fitted by multiple linear regression to indicator variables for demographics, metabolic control, treatments, complications, and comorbidities. Ethics approval was granted by local committees of the 306th Hospital of People's Liberation Army, and all participants provided written informed consent. Findings: Between March 1, 2015, and Nov 15, 2015, we enrolled 1070 outpatients and 684 inpatients (mean 57·9 years, SD 11·4). Mean 6 month total direct medical costs per patient were US1612·3 (SD 1735·6, median 1207·4, IQR 562·5–2105·9; US1·0=CNY 6·2 as of March, 2015) overall, 995·1 (1434·8; 704·8, 345·0–1196·6) for outpatients, and 2660·3 (1714·4; 2244·3, 1702·3–3089·4) for inpatients. Outpatient costs were 833·2 (909·3; 641·2, 345·6–1056·9) overall, 843·6 (940·4; 683·8, 336·7–1111·6) for outpatients, and 815·6 (854·5; 566·3, 364·1–981·3) for inpatients. 567 (41%) of 1384 participants who completed the study (54 [6%] of 871 outpatients and 513 [100%] of 513 inpatients) had 634 hospital admissions (62 for outpatients and 59 readmissions for inpatients) during the 6 month study period. Mean hospital stay expenses were 1700·7 (SD 1405·1, median 1438·0, IQR 1097·5–1946·0) overall, 2127·1 (3149·5, 1335·9, 665·5–2285·1) for outpatients, and 1654·4 (1052·1, 1442·8, 1104·8–1939·5) for inpatients. For 6 month total direct medical costs, the proportions of out-of-pocket payments were 41·5% (405·4) overall, 45·4% (394·9) for outpatients, and 34·9% (963·6) for inpatients. For outpatient medical costs, these proportions were 52·0% (605·7) overall, 46·2% (339·5) for outpatients, and 61·8% (518·4) for inpatients. For hospital stay expenses, these proportions were 25·7% (437·2) overall, 37·1% (788·6) for outpatients, and 24·1% (399·2) for inpatients. For inpatients, out-of-pocket payment accounted for 22·8% (366·8) of mean hospital stay expense due to diabetes. Medical costs incurred at each centre differed substantially. Mean 6 month costs per person were lowest at centre 11 (Wuhan, 891·5 [SD 1133·0]) and highest at centre 14 (Shenyang, 2475·9 [1534·0]) for total direct costs, lowest at centre 11 (Wuhan, 258·7 [157·0]) and highest at centre 1 (Beijing, 1582·2 [1939·2]) for outpatient costs, and lowest at centre 13 (Wulumuqi, 813·8 [397·3]) and highest in centre 9 (Chengdu, 2907·1 [3890·0]) for hospital stay expenses. Per-person out-of-pocket payment also varied widely across centres, being lowest at centre 11 (Wuhan, 72·3 [SD 114·8]) and highest at centre 15 (Changsha, 1357·9 [1219·6]) for 6 month total costs, lowest at centre 10 (Tianjin, 134·0 [134·3]) and highest at centre 15 (Changsha, 906·0 [853·9]) for outpatient costs, and lowest at centre 14 (Shenyang city, 0·93 [7·11]) and highest at centre 9 (Chengdu, 1944·4 [3807·8]) for mean hospital stay expenses. Duration of diabetes, treatment with lipid-lowering agents, HbA1c, diabetic kidney disease, diabetic neuropathy, and cardiovascular disease were each associated with a 20–40% increase in cost. Diabetes treatments were associated with a cost increase of 1·5–4·0 times. Compared with centre 11, the increases in cost associated with diabetes treatment were 24·0% at centre 13, 102·5%at centre 14, and 80·7% at centre 16. Interpretation: Diabetes treatment, particularly for glucose control and diabetes complications, substantially increases direct medical costs of type 2 diabetes. As different health policies and regional health inequalities have important effects on direct medical costs, health-care reform needs to optimise resource allocation in health service delivery systems and provide more equitable health care. Funding: Wu Jieping Medical Foundation.